Impaired responsiveness of platelets to epinephrine due to α2A adrenoreceptor deficiency in Male Chinese. (17th February 2016) - Lin, Tsun-Mei; Lin, Jih-Shyan; Tseng, Jen-Yu; Wu, Shang-Yin; Chen, Tsai-Yun
Abstract: Epinephrine is known as a weak, but important, agonist for platelet activation. It has been reported that the responsiveness of platelets to epinephrine was markedly impaired in 6% of Caucasians and in 16% of Japanese. The purpose of this study was to screen and characterize this abnormality in healthy Taiwanese Chinese volunteers. We used aggregometry, flow cytometry and platelet function analyzer (PFA)-100 system to assess in 50 healthy male volunteers the responsiveness of platelets to epinephrine stimulation. Using α2A adrenoceptor antagonist BRL44408 maleate competition and a [ 3 H]yohimbin binding assay, we evaluated α2A adrenoceptors on platelets. The aggregation of platelets after stimulation with 10 μM of epinephrine indicated two distinct groups of study participants: 24 (48.0%) good- and 26 (52.0%) impaired-responders to epinephrine. Flow cytometric analysis of platelets after stimulated with 1 μM epinephrine showed that glycoprotein (GP) IIb/IIIa and P-selectin expression of epinephrine good- and impaired-responders were 27.1 ± 11.0% vs. 9.9 ± 5.4% ( p  = 0.003) and 12.2 ± 6.2% vs. 3.6 ± 3.5% ( p  < 0.001), respectively. The PFA-100 system showed that epinephrine-impaired-responders had a longer collagen-epinephrine induced closure time. Good-responder platelets incubated with BRL44408 maleate had an impaired response to epinephrine stimulation. [ 3 H]yohimbine binding studies showed fewer α2A adrenoreceptors on the platelets of epinephrine-impaired-responders than on those of good-responders. The prevalence of impaired responsiveness to epinephrine was high and probably due to α2A adrenoreceptor deficiency in male Taiwanese Chinese.